Pelatihan Hadrah Al-Banjari untuk Meningkatkan Semangat dalam Kegiatan Rutinan Malam Jum’at Pembacaan Maulid Diba’ di Desa Sladi Kecamatan Kejayan - Muhammad Bustomy; Nelud Darajatul Aliyah (Fakultas Teknik Universitas Cenderawasih, 2024)
Albanjari has become an extracurricular that dominates and has quite a lot of enthusiasts, especially in Sladi village, Kejayan subdistrict, Pasuruan regency. Usually mothers use al-banjari as an accompaniment to the routine Friday night reading of Diba's birthday. However, the lack of understanding and skills in innovating rhythm and tone makes al-banjari activities felt less effective. This is because there is no special training accompanied by related parties who have more mastery of the banjari art. So in this case there is a need for al-banjari training to increase the understanding and creativity of mothers in Sladi village, Kejayan District in using al-banjari. Based on the al-banjari training carried out in Sladi Village, Kejayan District during community service activities in 2024, the following results were obtained: a) Increased understanding and skills of mothers in Sladi Village, Kejayan District, Pasuruan Regency in using al-banjari. b) Increased enthusiasm of the mothers in Sladi village, Kejayan District, Pasuruan Regency in the routine Friday night reading of Diba's birthday.